UPAYA MENGATASI RASA KANTUK DI KELAS DALAM PROSES BELAJAR MAHASISWA TARUNA AKADEMI MARITIM DJADAJAT - Triamiyono, Heru (Jurnal Ilmiah Widya, 2014)
Drowsiness becomes an obstacle for students who follow the teaching-learning process in the classroom that have an impact on the results of the study to be unfocused and unable to learn properly. The purpose of this research was to discuss: (1) the reasons of drowsiness of the students while following the lecture, (2) to find out the effort of overcoming the drowsiness of the students while following the lecture. This research is a case study conducted at a Maritime Academy midshipman Djadajat Jakarta with samples of 30 students from the Maritime Academy Djadajat. The collection of data using questionnaires and interviews. The results showed that: (1) the reasons of the students drowsiness caused by factors students less of rest (sleep) at night, doing unproductive activity, even due to too much sleep and eating too much, (2) an attempt or a solution to overcome the drowsiness while following a lecture in the classroom was out of the classroom, face wash, drinking coffee, doing light activities. As the preventive action, the students must perform their activities in accordance with the provisions of good health and properly.